2017
DOI: 10.1177/1479164117728014
|View full text |Cite
|
Sign up to set email alerts
|

High burden of coronary atherosclerosis in patients with a new diagnosis of type 2 diabetes

Abstract: Asymptomatic patients with newly diagnosed type 2 diabetes had plaque features associated with increased vulnerability as compared with age- and sex-matched controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 40 publications
(60 reference statements)
1
18
0
Order By: Relevance
“…Elevated blood glucose level combined with dyslipidemia increases atherosclerosis-related inflammation and makes it more extensive [ 41 ]. A larger extent of coronary artery calcification in asymptomatic patients with newly-diagnosed T2DM has been demonstrated [ 42 ]. Dyslipidemia is not only an important risk for macrovascular complications [ 43 ]; studies have also observed the association of dyslipidemia with microvascular complications related to T2DM namely diabetic retinopathy, diabetic nephropathy and diabetic neuropathy [ 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated blood glucose level combined with dyslipidemia increases atherosclerosis-related inflammation and makes it more extensive [ 41 ]. A larger extent of coronary artery calcification in asymptomatic patients with newly-diagnosed T2DM has been demonstrated [ 42 ]. Dyslipidemia is not only an important risk for macrovascular complications [ 43 ]; studies have also observed the association of dyslipidemia with microvascular complications related to T2DM namely diabetic retinopathy, diabetic nephropathy and diabetic neuropathy [ 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…16 Arterial thickening/hardening of the arteries or plaque makes the blood flow reduction , reducing the supply of oxygen and nutrients to the leg muscles. [17][18][19][20] Tissue necrosis can occur due to reduced blood flow, hypoxia, so that infection and gangrene can occur and that may lead to amputation. 21…”
Section: Itemsmentioning
confidence: 99%
“…In terms of plaque constitution, previous studies reported that 34% and 41% of plaques were classified as noncalcified plaque, proportions that are higher than those of 21% and 24% in nondiabetic patients [ 6 13 14 ]. These noncalcified plaques were associated with a family history of diabetes, and newly diagnosed patients tended to have a large volume of noncalcified plaque, especially patients with asymptomatic diabetes [ 15 16 ]. Asymptomatic diabetic patients therefore appear to have a relatively high prevalence of noncalcified plaques, with these being mainly nonobstructive.…”
Section: The Characteristics Of Coronary Atherosclerosismentioning
confidence: 99%
“…Diabetic patients are characterized by the presence of an accelerated progressive atheroma burden with a significantly increased incidence of CV events [ 20 ]. A recent study reported that asymptomatic patients with newly diagnosed diabetes had plaque features associated with increased vulnerability [ 16 ], a finding that indicates that early-stage diabetic patients constitute an important therapeutic target for the prevention of future CV events. Several studies have investigated the predictors of atherosclerosis progression and the impact of atherosclerosis progression on CV events in diabetic patients.…”
Section: Progression and Predictors Of Subclinical Coronary Atherosclmentioning
confidence: 99%